GAMBARAN TINGKAT PENGETAHUAN DAN KEPATUHAN SISWA/SISWI TERHADAP PROTOKOL KESEHATAN COVID-19 DI MAN (MADRASAH ALIYAH NEGERI) KOTA SINGKAWANG - Fitri Sri Rizki; Chisca Novianti (Akademi Farmasi Yarsi Pontianak, 2022)
Covid-19 is an infectious disease caused by a new strain of corona virus with common symptoms of fever, fatigue, coughing, seizures and diarrhoea. Complications from covid-19 occur in respiratory disorders such as acute respiratory failure, pneumonia, acute distress syndrome (ards), and asa result of the adverse effects of death. A person with a high level of knowledge is no doubt aware of the importance of taking care of one's health by obeying health protocols. That's why we need to break the chain that causes the covid-19 virus in an obedient manner. The purpose of inin research is to learn the level of knowledge and students' response to the covid-19 health protocol in the city of singkawang. Data collection is done by filling an angket or questionnaire that contains questions about the level of student knowledge and obedience overview. The sample was used by as many as 100 students/students of the singkawang city man. From the data obtained that there are still many students who do not understand health initiatives that have not adopted the new habit. There are 82% of students who know about covid-19 but as many students have not complied with the application of the new custom of covid-19 as of 43,33%.